Step-by-step explanation:
(x - 2)(2x + 3)
=2x²+3x-4x-6
=2x²-x-6
<span>2x^2 - 2x - 1 = 0 a = 2, b = -2, c = -1 b^2 - 4ac = (-2)^2 - 4(2)(-1) = 4 + 8 = 12
so the answer is 12
</span>
(1) y² + x² = 53
(2) y - x = 5 ⇒ y = x + 5
subtitute (2) to (1)
(x + 5)² + x² = 53 |use (a + b)² = a² + 2ab + b²
x² + 2x·5 + 5² + x² = 53
2x² + 10x + 25 = 53 |subtract 53 from both sides
2x² + 10x - 28 =0 |divide both sides by 2
x² + 5x - 14 = 0
x² - 2x+ 7x - 14 = 0
x(x - 2) + 7(x - 2) = 0
(x - 2)(x + 7) = 0 ⇔ x - 2 = 0 or x + 7 = 0 ⇔ x = 2 or x = -7
subtitute the values of y to (2)
for x = 2, y = 5 + 2 = 7
for x = -7, y = 5 + (-7) = 5 - 2 = 3
Answer: x = 2 and y = 7 or x = -7 and y = 3
The value of 4 is 4000, this is because it is in the thousands column (units,tens,hundreds,thousands etc)
Answer:
The solution lies at approximately (4.25,6.5).
Step-by-step explanation:
The estimate is pretty close for both equations. For the first equation, the estimate results in a value that is only 0.2125 units away from the constant. For the second equation, the estimate results in a value that is only 0.25 units away from the constant.